Menakar Eksistensi Penyuluh Agama Islam Di Era Milennial - Fawait Syaiful Rahman (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2020)
Abstract The millennial era is a continuation of the globalization era as well as becoming a new era of challenges. Anyone who can make good use of it can become a great opportunity so that the challenge brings blessings. Conversely, for people who cannot utilize properly and appropriately, in navigating the ark of life this can experience failure and even deterioration. People who can turn challenges into opportunities will succeed in achieving life's ideals, reach their material and spiritual life well-being, and proportionally position their physical and spiritual needs. To help people who are not good at maximizing opportunities and challenges, especially in the millennial era, Islamic Extensiontake full responsibility and contribute to be part of the government to produce a generation ofWorkersmorality, smart, smart, devoted to achieving a noble life. This article uses qualitative research with a literature study approach. A literature study is a study conducted with a focus on books, scientific works such as journals, and various other scientific writings. This article concludes that the existence of Islamic Extension Workers in the middle of the community is very strategic with several potentials. First, PAI's strategic position helps to explore various information that is directly experienced by the community. Second, PAI's strategic position helps to understand the different characters of the community and requires handling different solutions. Third, it helps the government to form a society that is virtuous, moral who are praiseworthy, devoted, love the motherland, productive, directing people to achieve world success until the hereafter.